Mechanism of action of sparfloxacin against and mechanism of resistance in gram-negative and gram-positive bacteria. - Piddock, L J (1991)
The inhibition of DNA synthesis by sparfloxacin; accumulation of sparfloxacin into members of the family Enterobacteriaceae, Pseudomonas aeruginosa, and staphylococci; induction of recA in Escherichia coli; and the optimum bactericidal concentration (OBC) were measured, and killing kinetics at the OBC were estimated. The OBC and maximum recA-inducing concentration in E. coli were both 1 microgram of sparfloxacin per ml. Accumulation was rapid; two- to threefold more sparfloxacin than ciprofloxacin accumulated in staphylococci and more sparfloxacin accumulated in staphylococci than in gram-negative bacteria. Laboratory mutants with decreased susceptibilities to quinolones alone or multiply resistant were selected from the Enterobacteriaceae and Staphylococcus aureus by using sparfloxacin.